(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
A total of 30 cases having bright echogenic liver on ultrasonography and raised ALT levels without Hepatitis B and Hepatitis C infection and without having history of alcohol consumption were referred to Gastroenterology department of BIRDEM Hospital and selected for liver biopsy in the study. The patients BMI and demographic profiles were recorded and necessary biochemical tests were carried out. After obtaining the histopathological reports, the correlation between different possible risk factors including biochemical findings and histological findings was sorted out. Based on BMI of Asian population, 73.4% of patients were over weight, 23.3% were obese and only 3.3% were with normal BMI. 90% patients presented with diabetes and 80% had some form of dyslipidaemia. 41% patients exhibited hypertriglycerdaemia, 21% had hypercholesterolaemia and both cholesterol and triglyceride were high in 34% patients. Histopathological study revealed that all 30 patients exhibited fatty change with macrovesicular type being the predominant. 43.3% patients had mild (<33%) steatosis and the rest 56.7% had moderate (33-66%) steatosis. In terms of staging of fibrosis in the liver, 83.3% exhibited stage-1 fibrosis and only 6.7% had stage-2 fibrosis. The rest 10% of the patients did not have any fibrosis. No correlation was established between hepatic enzyme levels (AST & ALT levels) and grading of steatosis & stage of fibrosis. Study of association between possible risk factors (Age, Sex, Diabetes Mellitus, Dyslipidaemia & BMI) and grading of steatosis and stage of fibrosis demonstrated that none of these risk factors was associated with those histological findings. Therefore it can be concluded that the patients presenting with bright echogenic liver on ultrasonography and elevated liver enzymes without having hepatitis B and hepatitis C infection and history of alcohol consumption are almost certainly to have Nonalcoholic fatty liver disease (NAFLD) specially if they are diabetic, dyslipidaemic and overweight or obese.The level of liver enzymes and the possible risk factors like age, sex, diabetes mellitus, dyslipidaemia and BMI do not seem to be good estimates of the severity of NAFLD. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12184 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 8-13